Corpus-based translation research: its development and implications for general, literary and Bible translation - A. Kruger (Acta Theologica)
Corpus-based translation research emerged in the late 1990s as a new area of research in the discipline of translation studies. It is informed by a specific area of linguistics known as corpus linguistics which involves the analysis of large corpora of authentic running text by means of computer software. Within linguistics, this methodology has revolutionised lexicographic practices and methods of language teaching. In translation studies this kind of research involves using computerised corpora to study translated text, not in terms of its equivalence to source texts, but as a valid object of study in its own right. Corpus-based research in translation is concerned with revealing both the universal and the specific features of translation, through the interplay of theoretical constructs and hypotheses, variety of data, novel descriptive categories and a rigorous, flexible methodology, which can be applied to inductive and deductive research, as well as product- and process-oriented studies. In this article an overview is given of the research that has led to the formation of a new subdiscipline in translation studies, called Corpus-based Translation Studies or CTS. I also demonstrate how CTS tools and techniques can be used for the analysis of general and literary translations and therefore also for Bible translations.